2019
DOI: 10.1016/j.adolescence.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Social media photos of substance use and their relationship to attitudes and behaviors among ethnic and racial minority emerging adult men living in low‐income areas

Abstract: Objectives: Emerging adult minority males have inequitable negative consequences from substance abuse. They are also frequent users of social media, logging into popular sites up to 25 times per week on average, so there may be opportunities to use these technologies for better understanding and preventing substance use behaviors. Through mobile phone monitoring, this study examined how social media sites are used to post substance use-related images and how posting such images is related to behaviors and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Among this sample of Dutch young people aged 12-30, alcohol posting among adolescents under age 18 (legal drinking age) was rare, but young adults endorsed mostly posting images that include alcohol for "entertainment" and choosing not to post alcohol-related images because they thought it was "stupid," because they drank little, to reduce risk of a future employer seeing it, and because it was not consistent with their identities (Hendriks et al, 2017). A distinction between legality or illegality of behavior is also relevant for marijuana depictions on social media, which an even larger majority of youth see as inappropriate to post (Lauckner et al, 2019). Nonetheless, when adolescents post about substance use on social media, posts are usually positive in nature, pro-alcohol posts outnumber anti-alcohol posts by a factor of more than 10, and negative consequences of use (e.g., hangovers or embarrassment) are rarely depicted (Cavazos-Rehg et al, 2015;Moreno et al, 2010Moreno et al, , 2013.…”
Section: Alcohol-and Drug-related Posting and Substance Use Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among this sample of Dutch young people aged 12-30, alcohol posting among adolescents under age 18 (legal drinking age) was rare, but young adults endorsed mostly posting images that include alcohol for "entertainment" and choosing not to post alcohol-related images because they thought it was "stupid," because they drank little, to reduce risk of a future employer seeing it, and because it was not consistent with their identities (Hendriks et al, 2017). A distinction between legality or illegality of behavior is also relevant for marijuana depictions on social media, which an even larger majority of youth see as inappropriate to post (Lauckner et al, 2019). Nonetheless, when adolescents post about substance use on social media, posts are usually positive in nature, pro-alcohol posts outnumber anti-alcohol posts by a factor of more than 10, and negative consequences of use (e.g., hangovers or embarrassment) are rarely depicted (Cavazos-Rehg et al, 2015;Moreno et al, 2010Moreno et al, , 2013.…”
Section: Alcohol-and Drug-related Posting and Substance Use Behaviorsmentioning
confidence: 99%
“…For tobacco, adolescents who posted positive tobacco-related content on Twitter were more likely to report past month cigarette and any tobacco use relative to those who did not post about tobacco on Twitter (Unger et al, 2018), and although posting about tobacco use is much less common than alcohol use among Dutch emerging adults, cigarette-related social media posts are nonetheless associated with real-life cigarette use (Van Hoof et al, 2014). For marijuana, research in young adults suggests that they do indeed post cannabis-related images on Instagram (Cavazos-Rehg et al, 2016) and that posting marijuana-related content to social media is associated with more pro-marijuana attitudes and actual marijuana use among racial-ethnic minority college students from lowincome areas; however, no such associations emerged for alcohol depictions, alcohol attitudes, and alcohol use, which may suggest that these associations are most relevant when a behavior is illegal or less normative (Lauckner et al, 2019). Recent research suggests that marijuana-related posting is not uncommon even in adolescence, however, which underscores the necessity of more research in this domain.…”
Section: Alcohol-and Drug-related Posting and Substance Use Behaviorsmentioning
confidence: 99%
“…In both adolescents and adults, exposure to digital alcohol marketing was found to be associated with drinking initiation among non‐drinkers (Anderson et al, 2009 ; Smith & Foxcroft, 2009 ), increased levels of consumption among drinkers (Anderson et al, 2009 ), and binge or hazardous drinking behavior (Noel et al, 2020 ). A recent study (Lauckner et al, 2019 ) found that 56% of young adults between the age of 18 and 25 report alcohol use, and 37% report binge drinking and are frequently exposed to alcohol images on social networking sites. To vie with the ever‐growing degree of alcohol advertising and alcohol‐related content on social networking sites, rapid screening tools need to be developed.…”
Section: Introductionmentioning
confidence: 99%